Status of metals in serum and urine samples of chronic kidney disease patients in a rural area of Bangladesh: An observational study - Tasrina Rabia Choudhury (Elsevier, 2021)
The traditional causes of Chronic Kidney Damage (CKD) are Diabetes and Hypertension. However, recent studies reported the possible relations between metal exposure and CKD. This study aims to explore the status of metals in CKD patients compared to their healthy counterparts at Narayanganj, Bangladesh, through a cross-sectional study. In this study, 50 volunteers were involved; 30 CKD patients and 20 healthy controls. Five metals were measured from serum [Copper (Cu) and Zinc (Zn)] and urine [Lead (Pb), Cadmium (Cd), and Chromium (Cr)] using Atomic Absorption Spectrometry. Compared to the controls the CKD patients exhibited significantly higher levels of Pb, Cd and Cr levels in their urine samples. This signifies a potential association between heavy metal exposure and CKD. The serum levels of Cu were much higher than expected for CKD patients than controls, and the Zn values were in accordance with established literature. However, the level of Zn in blood was significantly lower in the CKD group compared to the control. This data suggests that the Cu imbalance in the serum of the CKD subjects might have been related to a myriad of reasons, the most plausible of which being exposed to large concentrations of the nephrotoxic metals such as Pb, Cd and Cr in this study. Our study has shed a much needed light on the correlation between CKD and exposure to heavy metals and imbalance of essential metals in blood serum, in a rural locality of Bangladesh.